(3x+5)(5x-2)=0

Simple and best practice solution for (3x+5)(5x-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5)(5x-2)=0 equation:


Simplifying
(3x + 5)(5x + -2) = 0

Reorder the terms:
(5 + 3x)(5x + -2) = 0

Reorder the terms:
(5 + 3x)(-2 + 5x) = 0

Multiply (5 + 3x) * (-2 + 5x)
(5(-2 + 5x) + 3x * (-2 + 5x)) = 0
((-2 * 5 + 5x * 5) + 3x * (-2 + 5x)) = 0
((-10 + 25x) + 3x * (-2 + 5x)) = 0
(-10 + 25x + (-2 * 3x + 5x * 3x)) = 0
(-10 + 25x + (-6x + 15x2)) = 0

Combine like terms: 25x + -6x = 19x
(-10 + 19x + 15x2) = 0

Solving
-10 + 19x + 15x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-5 + -3x)(2 + -5x) = 0

Subproblem 1

Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667

Subproblem 2

Set the factor '(2 + -5x)' equal to zero and attempt to solve: Simplifying 2 + -5x = 0 Solving 2 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = 0 + -2 -5x = 0 + -2 Combine like terms: 0 + -2 = -2 -5x = -2 Divide each side by '-5'. x = 0.4 Simplifying x = 0.4

Solution

x = {-1.666666667, 0.4}

See similar equations:

| 4+2(7r-4)=-116 | | 2=0.15x^2+1 | | (((2z)^(1/5))^4)/(z^(1/20)) | | 4+2(7r-r)=-116 | | 5=0.55x^2+1 | | (((2z)^(1/5))^4)/z^(1/20) | | 2.70=0.55x^2+1 | | -2x-3y=-5 | | -5(4n-4)=40 | | -5h=-20 | | 4(x-1)=2(-x) | | 4p^2+11p-45=0 | | 6(2v-2)=96 | | 40b+10=210 | | (2x+10)+5x+140= | | 3(8-4x)=84 | | 4x-13-35=0 | | 3x+90=450 | | 2(x+5)(x-1)= | | 7+9+n=-9+2n+n | | 4*x^2+4*y^2-y^3=0 | | 4c-36=-8 | | y+26-8=40 | | 93=16-5p | | -12x-4=56 | | 6k-15=-33 | | 5x^2+y^2=21 | | 6x-3=17+4x | | 12/21 | | (x-3)2=12 | | 88/8 | | log(2)(5x-5)=4 |

Equations solver categories